2011
DOI: 10.1016/j.cub.2011.10.040
|View full text |Cite
|
Sign up to set email alerts
|

The P4-ATPase TAT-5 Inhibits the Budding of Extracellular Vesicles in C. elegans Embryos

Abstract: Summary Background Cells release extracellular vesicles (ECVs) that can influence differentiation, modulate the immune response, promote coagulation, and induce metastasis. Many ECVs form by budding outwards from the plasma membrane, but the molecules that regulate budding are unknown. In ECVs, the outer leaflet of the membrane bilayer contains aminophospholipids that are normally sequestered to the inner leaflet of the plasma membrane, suggesting a role for lipid asymmetry in ECV budding. Results We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
205
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(216 citation statements)
references
References 42 publications
9
205
0
2
Order By: Relevance
“…In yeast, the major phenotype associated with loss of P4-ATPase function is abnormal transport vesicle budding from the transgolgi network (19,33,34). Similar defects in cargo sorting have been observed in Caenorhabditis elegans Tat-1 mutants (35), and other C. elegans P4-ATPase mutants are defective for phagocytosis of dead cells and regulation of ectosome production (35)(36)(37)(38). Proper lipid localization may be required for vesicle docking or receptor recycling leading to reduced receptor levels in the cilia.…”
Section: Discussionmentioning
confidence: 76%
“…In yeast, the major phenotype associated with loss of P4-ATPase function is abnormal transport vesicle budding from the transgolgi network (19,33,34). Similar defects in cargo sorting have been observed in Caenorhabditis elegans Tat-1 mutants (35), and other C. elegans P4-ATPase mutants are defective for phagocytosis of dead cells and regulation of ectosome production (35)(36)(37)(38). Proper lipid localization may be required for vesicle docking or receptor recycling leading to reduced receptor levels in the cilia.…”
Section: Discussionmentioning
confidence: 76%
“…36) supporting an MVB fusion origin. However, we have also observed a decrease in signalling and Hh release when interfering with P4-ATPase (CG31729), the Drosophila orthologue of TAT-5 specifically involved in the formation of ectosomes in C. elegans 24 . Thus, as it is difficult to account for the considerable differences between the two types of vesicles, the result of knocking down Vps22 and P4-ATPase together with the EM data and the in vivo imaging indicate that Hh might be released in both ectosomes/microvesicles and exosome-like vesicles.…”
Section: Discussionmentioning
confidence: 93%
“…Although shedding vesicles/ectosomes seem to have a different origin 31 , the mechanisms of their sorting process remain obscure and might also be dependent on the ESCRT complex 24 . In addition, studies have shown a crucial role for cholesterol-rich microdomains of the plasma membrane for shedding vesicle formation 32 as well as for biogenesis of exosomes 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether ARMMs production also requires ESCRT-III and ALIX which are involved in Gag-mediated HIV budding (46), is not known at present. Recently, the shedding of ESCRT-dependent microvesicles that may prove to be ARMMs has been found to be increased in Caenorhabditis elegans embryos by loss of the evolutionarily conserved P4-ATPase, TAT-5, and consequent exposure of phosphatidylethanolamine at the cell surface (47).…”
Section: Discussionmentioning
confidence: 99%